Lignin catabolic pathways reveal unique characteristics of dye‐decolorizing peroxidases in Pseudomonas putida. (29th April 2019) - Lin, Lu; Wang, Xiaopeng; Cao, Lanfang; Xu, Meiying
Summary: Lignin is one of the largest carbon reservoirs in the environment, playing an important role in the global carbon cycle. However, lignin degradation in bacteria, especially non‐model organisms, has not been well characterized either enzymatically or genetically. Here, a lignin‐degrading bacterial strain, Pseudomonas putida A514, was used as the research model. Genomic and proteomic analyses suggested that two B subfamily dye‐decolorizing peroxidases (DypBs) were prominent in lignin depolymerization, while the classic O2 ‐dependent ring cleavage strategy was utilized in central pathways to catabolize lignin‐derived aromatic compounds that were funnelled by peripheral pathways. These enzymes, together with a range of transporters, sequential and expression‐dose dependent regulation and stress response systems coordinated for lignin metabolism. Catalytic assays indicated these DypBs show unique Mn 2+ independent lignin depolymerization activity, while Mn 2+ oxidation activity is absent. Furthermore, a high synergy between DypB enzymes and A514 cells was observed to promote cell growth (5 × 10 12 cfus/ml) and lignin degradation (27%). This suggested DypBs are competitive lignin biocatalysts and pinpointed limited extracellular secretion capacity as the rate‐limiting factor in bacterial lignin degradation. DypB production was, therefore, optimized in recombinant strains and a 14, 141‐fold increase in DypB activity (56, 565 U/l) was achieved, providing novel insights for lignin bioconversion.